Multicultural teams: Does national diversity associate with performance in professional soccer? - Thadeu Gasparetto (PLoS ONE, 2025)
This study examines whether the national diversity of players in multicultural teams affects the performance of professional soccer clubs. I analyze data from the top-tier leagues of six European countries – England, Belgium, Germany, Cyprus, Latvia, and the Netherlands – covering the 2015/2016–2020/2021 seasons. These leagues were selected because they impose no limits on the number of foreign players in senior squads, providing a clear view of this phenomenon. Using Ordinary Least Squares (OLS) estimations in a forward stepwise approach, I find that national diversity does not correlate with club performance. However, the total number of foreign players is positively associated with performance, with each additional foreign player correlating with a 0.42% increase in win percentage. Moreover, the most complete model also indicates that an additional domestic league title is associated with a 0.99% increase in win percentage per title, while participation in the UEFA Champions League is associated with a 13.6% higher win percentage. Future research should explore the causal mechanisms underlying this relationship, examining how specific attributes of foreign players, such as playing style and experience, contribute to performance. Additionally, studies could investigate how management practices, particularly the adaptation of foreign players to a new country and culture, influence their impact on club success.